OC-040 Regular nutritional blood test monitoring in children on home enteral tube feeding—is this necessary?. (28th May 2012) - Lim, Y; Paxton, C; Wilson, D
Abstract : Introduction: The use of home enteral tube feeding (HETF) in children with chronic illness is increasing. 6-monthly nutritional blood test monitoring (NBTM) while on HETF is recommended by BAPEN for adults; there is minimal evidence to inform guidelines regarding the biochemical monitoring of children on long-term HETF. Aim: To provide evidence for or against the practice of 6-monthly NBTM in children receiving HETF. Methods: We performed a retrospective review of all children age <18 years, who were started on HETF from 01 January 2005 to 30 June 2010 by the nutrition support team (NST) in the Royal Hospital for Sick Children, Edinburgh. Patients who received <2 months of HETF, or failed to receive more than one set of NBTM within the 1st year of starting HETF were excluded. Comparison of baseline NBTM results with results at 6–12 months after the start of HETF were made. Our NBTM profile includes full blood count, renal profile, bone profile, liver function tests, folate, ferritin, vitamin B12, fat-soluble vitamins and trace elements (Se, Cu, Zn). Results: 42 children were included in the study; none developed refeeding syndrome. 37 (88%) had NBTM performed within 6 months of commencing HETF, 19 (45%) at 6 months after commencing HETF, and 21 (50%) at 1 year after commencing HETF. Significant abnormal parameters identified prior to commencing HETF included low Hb levels (32%), low ferritin levels (31%) and low folate levels (25%). Small groups of between 8% and 10% had low levels of trace elements (Se and Cu) and vitamin D levels. At 6 months and 1 year after start of HETF, there was a small increase of children with low Hb levels (40%) but an improvement in those with low ferritin (14%) and low folate levels (6%). 4% of the study had low vitamin D, and/or trace element (Zn, Cu, Se) levels. There were no toxic levels of vitamins or trace elements within 12 months of start of HETF. Trend comparison was performed in 25 children who had NBTM both before and within a year of commencing HETF. None of the children developed toxic levels of trace elements, one child developed high trace element levels (Se) and another continued to have high Se levels after starting HETF. None of the children developed toxic or high levels of fat soluble vitamins. There were no worryingly low micronutrient levels in any of the 25 children after the start of HETF. Conclusion: Children on HETF in our study maintain and had improvement of their micronutrient status after start of HETF. Six monthly blood test monitoring may only be necessary in special circumstances (refeeding syndrome, frankly deficient or toxic micronutrient levels at start of HETF) and may not significantly enhance the overall nutritional monitoring and management of all children on HETF. Competing interests: None declared.